2004
DOI: 10.1007/s00360-003-0396-y
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin induces proliferation and Ca 2+ -influx in specific leukocyte subpopulations of rainbow trout ( Oncorhynchus mykiss ) blood and head kidney cells

Abstract: In mammals, erythropoietin regulates the development and differentiation of erythrocytes. Although hematopoietic cells of bony fish correspond in their ontogeneic development, morphology, and function to their mammalian counterparts, an erythropoietin (EPO)-like molecule has not been identified. In this study we present evidence for a mitogenic response of blood and head kidney leukocytes of rainbow trout after stimulation by recombinant human EPO (rhu EPO). The modulation of cellular activities is accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Both GH and prolactin, in addition to erythropoietin [ 37 ] and leptin, have been classified amongst the short-chain cytokines of the type 1 cytokine family, which supports the dual role of GH as a hormone and a cytokine (for further reading, see [ 38 ]).…”
Section: Gh and Igf-i Actions In Bony Fish Immune Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…Both GH and prolactin, in addition to erythropoietin [ 37 ] and leptin, have been classified amongst the short-chain cytokines of the type 1 cytokine family, which supports the dual role of GH as a hormone and a cytokine (for further reading, see [ 38 ]).…”
Section: Gh and Igf-i Actions In Bony Fish Immune Responsesmentioning
confidence: 96%
“…Large and small lymphocytes also showed appreciable staining while no binding was detected in thrombocytes [ 21 ], which have been recently demonstrated to be capable of acting as phagocytic immune cells in teleost fish [ 72 ]. Interestingly, in rainbow trout, erythroid cells and also a subpopulation of B-lymphocytes responded to erythropoietin, while granulocytes and thrombocytes did not [ 37 ]. Thus, more studies are needed on stimuli of immune cell lineage differentiation and proliferation.…”
Section: Regulation Of Igf-i In Fish Immune Organs and Cells By Ghmentioning
confidence: 99%
“…Thus, a possible explanation would be that Epo deficiency affects the coupling between astrocytes and neurons in this medullary area. In support of this hypothesis, it has been shown that RTN/pFRG astrocytes responded to physiological decreases in pH with vigorous elevations in intracellular Ca 2+ ( Gourine et al, 2010 ) and that Epo regulates Ca 2+ transport in cells ( Körbel et al, 2004 ). It is thus possible that Epo deficiency alters the capacity of RTN/pFRG astrocytes to detect the CO 2 /H + -elevation and thus to excite RTN/pFRG neurons.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to its well known role in erythropoiesis however a diverse array of cells have now been identified that produce Epo and/or express the Epo receptor including endothelial cells, smooth muscle cells and cells of the central nervous system (Digicaylioglu et al, 1995;Masuda et al, 1994). In vitro Epo has been shown to regulate a variety of neural functions such as calcium flux (Korbel et al, 2004) neurotransmitter synthesis and cell survival (Velly et al, 2010;Vogel et al, 2003). Furthermore Epo has neurotrophic effects (Chen et al, 2007;Grimm et al, 2002;Junk et al, 2002), can induce an angiogenic phenotype in cultured endothelial cells, is a potent angiogenic factor in vivo (Ribatti et al, 2003) and enhances ventilation in hypoxic conditions (Soliz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%